Difference Research on the Influence of Government Audit on the Performance of State-Owned Enterprises: – A Case Study of A-Share Listed State-Owned Enterprises - Wang, Zhelin (Transactions on Economics, Business and Management Research, 2024)
After collecting the relevant literature on how the government audit impacts the performance of state-owned enterprises, this study compares the differences in the impact of government audit on the performance of state-owned enterprises in various regions and sizes, and collects 8090 data from a number of A-share listed state-owned enterprises for empirical analysis. According to the empirical results, government audits can promote the performance of state-owned enterprises, and such an influence is different in various regions and scales of state-owned enterprises. Further research shows that compared with the state-owned enterprises in the eastern region, the government audits can better promote the performance of the state-owned enterprises in the central and western regions. Compared with small-scale state-owned enterprises, government audits can better promote the performance of large-scale state-owned enterprises. Finally, this paper provides corresponding suggestions on how to conduct government audits in the central and western regions and small-scale state-owned enterprises.